Wakaf Aset Digital: Non Fungible Token (NFT) - Muhammad Labib Fahmi Arif (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Non-Fungible Token (NFT) is a digital asset based on blockchain, in the form of a unique certificate or token in digital form that cannot be replaced with another, which is unique and immutable and represents ownership of an asset. NFT has many benefits, especially in economy, so, NFT used as a medium for many social activities. On the other hand, Islam strongly supports social activities, one of which is waqf instruments. The characteristics of NFT which are enduring and have long-term economic benefits, are compatible with the concept of waqf. However, as a new innovation, NFT has not been widely studied according to sharia, especially as object of waqf. On that basis, this study tries to explore whether NFT can be used as an object of waqf and create a concept for it. Therefore, this research is included in normative legal research, and using a conceptual approach and analytical descriptive analysis. And result of this study is: 1) in terms of fiqh, NFT can be used as a waqf object as well as copyright as a waqf object, of course with due regard to the three halalness foundation of the NFT and the fulfillment of its requirements for the object of waqf. 2) In practice, wakif for NFT is the creator, while mauquf is in the form of copyright contained in the NFT which is owned by the creator, and the proceeds will be donated to mauquf 'alaih in the form of royalties that arise from the copyright.